Prevalência da colonização por Streptococcus do grupo B nas grávidas do CHUSJ - Santos,Ricardo (2020)
Overview and Aims: Colonized pregnant women with group B streptococcus (GBS) are generally asymptomatic, but GBS can cause urinary tract infection, as well as amnionitis, endometritis and bacteraemia. It is also associated with an increased risk of preterm birth and fetal death. In the newborn, GBS is the main cause of infection, which can lead to neonatal GBS early-onset disease (EOD) or late-onset disease. The aim of this study was to evaluate the prevalence of GBS colonization in pregnant women, and to assess differences between groups, risk factors for colonization, and the occurrence of EOD. Study Design, Population and Methods: An observational, retrospective and descriptive study was carried out in pregnant women who had deliveries between January 2013 and September 2019. We evaluated demographic and clinical variables obtained from electronic files. The pregnant women were divided into two groups, colonized by GBS and not colonized by GBS. Descriptive analyses of the study variables and statistical tests were performed to assess risk factors for GBS colonization and to compare means and distributions between colonized and non-colonized pregnant women. Results: A total of 12,315 cases were included in the study. 2,211 pregnant women were colonized by the SGB, corresponding to a prevalence of 18% (95% CI: 17.3 - 18.6). Differences were found for maternal age, educational levels, previous births and pregnancies, weight gain during pregnancy and gestational age. An association was verified between urinary infections during pregnancy and colonization. We identified a prevalence of neonatal GBS EOD of 2.3 per 1000 live births in the colonized group. Conclusions: The prevalence of GBS colonization is similar to that previously reported. The prevalence of EOD in colonized pregnant women is also in accordance with other studies, reflecting the importance of universal screening for GBS and antibiotic prophylaxis.